Meaning in Life Among Patients With Chronic Pain and Suicidal Ideation: Mixed Methods Study - Costanza, Alessandra; Chytas, Vasileios; Piguet, Valérie; Luthy, Christophe; Mazzola, Viridiana; Bondolfi, Guido; Cedraschi, Christine (JMIR Formative Research, 2021)
Background Patients with chronic pain have elevated risk of suicidal ideation and behavior, including suicide attempts and completed suicides. In most studies, associations between chronic pain and suicidal ideation/suicidal behavior are robust even after adjusting for the effect of sociodemographics and psychiatric comorbidity. However, to refine the risk profile of these patients, further exploration of other possible risk and protective factors is necessary. Objective There is a common clinical observation that experiencing chronic pain often requires a revision of life goals and expectations, and hence, it impacts the existential domain including one’s perception of the meaning in life (MiL). This study aimed to characterize the main domains that constitute the personal MiL, including the “presence of” and “search for” constructs, in a group of patients with chronic pain and suicidal ideation. Methods Seventy participants were enlisted by ongoing recruitment through a larger project anchored in daily clinical practice at the Multidisciplinary Pain Center of the Geneva University Hospitals. It was an observational mixed method study. Data were recorded through both validated quantitative questionnaires and qualitative open-ended questions. Results The total sample consisted of 70 patients. Responses to questionnaires showed a depressive episode in 68 (97%) patients and anxious disorders in 25 (36%) patients. With a score threshold for positive MiL of 24, the mean score for the “presence of” construct was 20.13 (SD 8.23), and 63% (44/70) of respondents had a score <24. The mean score for the “search for” construct was lower at 18.14 (SD 8.64), and 70% (49/70) of respondents had a score <24. The “presence of” and “search for” constructs were significantly positively correlated (R=0.402; P=.001). An open question addressed the “presence of” construct by inviting the respondents to cite domains they consider as providing meaning in their life at the present time. All patients responded to this question, citing one or more domains. The three main dimensions that emerged from content analysis of this qualitative section were as follows: the domain of relationships, the domain of personal activities, and pain and its consequences on MiL. Conclusions The study results provide insights into patients with chronic pain and suicidal ideation, including the domains that provide them with meaning in their lives and the impact of pain on these domains with regard to suicidal ideation. The main clinical implications concern both prevention and supportive/psychotherapeutic interventions. They are based on a narrative approach aiming to explore with the patients the content of their suffering and the MiL domains that they could identify to mitigate it, in order to restructure/reinforce these domains and thus possibly reduce suicidal ideation. Specifically, a focus on maintaining the domains of interpersonal relationships and personal activities can allow patients to ultimately escape the biopsychosocial vicious cycle of chronic pain–induced deep moral suffering.